Arecoline attenuates memory impairment and demyelination in a cuprizone-induced mouse model of schizophrenia. Issue 2 (16th January 2019) - Xu, Zhizhong; Adilijiang, Abulimiti; Wang, Wenqiang; You, Pan; Lin, Duoduo; Li, Xinmin; He, Jue
Abstract : Cerebral demyelination is possibly one of the main pathological factors involved in the development of schizophrenia. Our previous studies have showed that Areca catechu nut extract could ameliorate cognitive decline by facilitating myelination processes in the frontal cortex in a cuprizone (CPZ)-induced mouse model of schizophrenia. The aim of the present study was to evaluate the effects of arecoline, one of the alkaloids in A. catechu nut extract, on memory impairment and cerebral demyelination in CPZ-treated mice. Mice were treated with CPZ (0 or 0.2%) in chow food and arecoline hydrobromide (0, 2.5, or 5 mg/kg/day) in drinking water for 12 weeks before Y-maze behavioral test. After the behavioral test, the mice were sacrificed for the measurement of myelin basic protein in the frontal cortex. We showed that arecoline-attenuated spatial working memory impairment, concurrent with attenuated demyelination related to vehicle-treated CPZ mice for the first time. Arecoline is one of the primary active ingredients in A. catechu nut responsible for attenuating memory impairment and demyelination in CPZ mice, cerebral demyelination may have a role in memory impairment, and modulation of cerebral demyelination could be a useful strategy in schizophrenia treatment.